The roles, threats and distribution of rodents in Malaysia / Fatin Afiqah Azhar and Mohamad Azam Akmal Abu Bakar - Azhar, Fatin Afiqah; Abu Bakar, Mohamad Azam Akmal (Universiti Teknologi MARA, Sabah, 2021)
Rodents are the world's largest group of small mammals with more than 2200 living species, comprising around 40 percent of all small mammal species existing today. Rodents are non-volant small mammals that weigh approximately less than 500g and inhabit various types of habitat such as grasslands, desert and even in human settlements. This review explained the roles, threats and distribution of rodents in the ecosystem they inhabit. Some species play critical roles as seed disperser, pollinator and even as laboratory subjects in many experiments. This article serves as an eye-opener about the rodent status distribution and abundance in natural and modified habitat, especially in Malaysia. This review of literature can provide knowledge to people to know more about rodents.